COVID-19 and Distance Learning: Effects on Georgia State University School of Public Health Students - Armstrong-Mensah, Elizabeth; Ramsey-White, Kim; Yankey, Barbara; Self-Brown, Shannon (Frontiers in Public Health, 2020)
On March 11, 2020, the World Health organization declared COVID-19 a global pandemic. Following the speed with which COVID-19 spread to all parts of the world, and to contain the spread of the disease, most governments around the world, including the US, authorized unprecedented social containment measures to stem the tide. These measures among others required social distancing and the temporary physical closure of educational institutions. The Georgia State University School of Public Health, like all other institutions of higher learning, had to create distance-learning opportunities to enable students to complete the 2019–2020 academic year. The unplanned, rapid, and uncertain duration of the approach presented challenges at all academic levels. Not much information on best practices was available to guide such abrupt transitions to college education. The purpose of the study was to collect data on how the transition to distance learning impacted undergraduate and graduate students taking courses in public health at GSU. The goal was to identify student academic challenges and the unforeseen benefits of distance learning, and to use that information to inform practices that can be implemented during crises that impact university education.